Exercise capacity in children with bronchopulmonary dysplasia at school age. (September 2020) - Prenzel, Freerk; Vogel, Mandy; Siekmeyer, Werner; Körner, Antje; Kiess, Wieland; vom Hove, Maike
Abstract: Objective: To assess the exercise capacity, exercise habits, and lung function of preterm born children with bronchopulmonary dysplasia (BPD) compared to term born controls at school age. Methods: Cardiopulmonary exercise test (CPET) by cycle ergometer and pulmonary function test were performed in children with BPD (n = 42) and compared with a term born control group (n = 42). Daily activity, participation in sports and respiratory symptoms were assessed by questionnaire. Results: Children with BPD versus controls had significantly lower values for oxygen consumption (V̇O2 [mL/min] 1442 ± 417 vs. 1766 ± 541), minute ventilation (VE [L/min] 48 ± 14.92 vs. 60 ± 18.33), and workload (W [watt] 96.1 ± 16.7 vs. 110.6 ± 17.2) at peak exercise and a lower anaerobic threshold (VO2 AT [mL/min] 1183 ± 345 vs. 1382 ± 398). When corrected for weight, only for the workload (2.7 ± 0.5 vs. 3.1 ± 0.5, p = 0.0013) did significant differences persist. The forced expiratory volume in 1 s and forced expiratory flow between 25 and 75% of expired forced vital capacity were significantly reduced in the BPD group (p < 0.0001). Children with BPD have a higher risk of reporting difficulties in physical activity (OR 2.5) and of suffering from wheezing or shortness of breath while exercising (OR 2.5). Conclusion: Compared to term born controls, children with BPD at school age show airflow obstruction, a lower workload in CPET, and more respiratory symptoms related to physical activity. The comparable oxygen consumption based on weight suggests a functionally normal alveolar compartment. Highlights: Preterm born children show airflow obstruction and have a lower workload in CPET. Children with BPD have more difficulties and report more respiratory symptoms during physical activity. Physical activity levels corresponded to the controls, and adjusted for weight, respiratory CPET values were equivalent. Relevant associations between the pulmonary function variables and the CPET parameters were not found. The duration of oxygen supplementation and birth weight were inversely associated with peak VO2 and workload.